2014
DOI: 10.1073/pnas.1406672111
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of bats at wind turbines

Abstract: Wind turbines are causing unprecedented numbers of bat fatalities. Many fatalities involve tree-roosting bats, but reasons for this higher susceptibility remain unknown. To better understand behaviors associated with risk, we monitored bats at three experimentally manipulated wind turbines in Indiana, United States, from July 29 to October 1, 2012, using thermal cameras and other methods. We observed bats on 993 occasions and saw many behaviors, including close approaches, flight loops and dives, hovering, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
236
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(250 citation statements)
references
References 47 publications
11
236
1
2
Order By: Relevance
“…Thus, Hein et al (2013) concluded that prediction of risk prior to construction of a wind facility is highly variable and imprecise and acoustic data may not necessarily predict bat fatality in any reliable way. One explanation as to why correlations between pre-construction measurements of bat activity with similar measurements made post-construction or fatality estimates are weak could be that bats are attracted to the turbines once they are built and sites are used differently by at least some species (open-air bats) afterward (Horn et al 2008;Kunz et al 2007b;Arnett et al 2008;Cryan et al 2014).…”
Section: Offshore Wind Facilitiesmentioning
confidence: 99%
“…Thus, Hein et al (2013) concluded that prediction of risk prior to construction of a wind facility is highly variable and imprecise and acoustic data may not necessarily predict bat fatality in any reliable way. One explanation as to why correlations between pre-construction measurements of bat activity with similar measurements made post-construction or fatality estimates are weak could be that bats are attracted to the turbines once they are built and sites are used differently by at least some species (open-air bats) afterward (Horn et al 2008;Kunz et al 2007b;Arnett et al 2008;Cryan et al 2014).…”
Section: Offshore Wind Facilitiesmentioning
confidence: 99%
“…Video recording observations combined with collection of GPS data improves the collection of precise data, both for identifying the species involved and for determining location and circumstances of the collisions (train speed, bird behavior, etc.). Techniques like video recording from fixed points, vehicles, or animal-borne cameras have been applied to study animal behavior and monitor wildlife (Whorff and Griffing, 1992;Thompson et al, 1999;Okuyama et al, 2015), but rarely to assess mortality risk (Desholm et al, 2006;Cryan et al, 2014;Furness, 2014;Doppler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of aviation warning lights on the turbines does not increase mortality rate (Johnson et al 2004 ;Bennett and Hale 2014 ); however a recent study has shown that tree roosting bat species from North America were attracted to the turbines (Cryan et al 2014 ). This attraction could be due to the visual confusion of the turbines silhouettes with trees, reinforced by other cues such as similar downwind airfl ow patterns.…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 96%